Women Participation in October 2019 Protests: A problematical existence issue in the public sphere - Hammadi, Ilham Makki (Al-Adab Journal, 2021)
In circumstances that have been characterized by violence and insecurity since the beginning of the protests against successive governments since 2003, Women's participation in protests has been steadily increasing and during their participation in October 2019 Protest they showed a great strength and courage, these women challenged the typical gender norms and the direct and structured Political violence against them. Women’s Participation in October Protest has been categorized by being out of Political and Partisan bias and also outside the accounts of the civil society organization in general. They adopted the slogans of revolutionary protests to counter the deterioration of the economic situation of a large segment of Iraq society, the corruption which is spreading in all branches of the government and the fragility of the polity with the illegal armed factions (militias groups). At the same time, women, especially young one’s have struggled to raise slogans of equal rights, defying relationships and dynamics (gender), and confusing the Patriarchate and its perceptions that women are not active and intruders in politics. During October 2019 protests, women and girls challenged traditional notions about the gender presence of women that the society restrict it into the private sphere, Despite the excessive use of force by security institutions and gender-based violence directed against women, their participation continued at the same pace and they supported the momentum of protests at the most difficult times. Individually and collectively, women have demonstrated their effectiveness, strength of mobilization, great impulse on demand and have played various roles both in the front lines with the security forces and in the back lines with their participation, support and encouragement for the protesters in the protests arenas. Women protesters, and especially young ones adopted new and diverse methods and strategies to demonstrate their presence and right to participate in the public sphere, which has long been considered an exclusive area of special interest to men. The stories of women confirmed the association of women's participation in October protests with the problem of stereotypical roles and the visible and public presence of women in the public sphere. Despite the apparent support of society for their participation, many women nevertheless faced significant constraints and challenges that affected their level of participation in the protests. Family consent to participation was the first challenge faced by women, especially young women, the stereotype of limiting women's role in care-giving within home to their lack of rational political awareness and decision-making power has been used as justification to prevent their participation in protests. Education, age, local social contexts, women's time in the public sphere and State violence all overlap and influence women's decisions and choices to participate in political life. Political violence against women has also contributed significantly to reducing their ability to participate in public and political life. It is increasingly clear that violence against women not only affects them in the private sphere, but can hamper their participation in the public sphere and in party-political life. Violence and political violence are used as punishment for women/victims to challenge the traditional boundaries of the public sphere, but regard all these boundaries the society puts, women proved their presence in October Protest and they used virtual reality and the webspace to express, share and confess their political views and perspectives, and so they changed the norms about their traditional political participation. Many women who have been interviewed confirmed that Social Media sites were a virtual space parallel to the protest arenas and it gave all women space and opportunity especially those who have been denied effective participation in protests due to discriminatory gender restrictions.